Keberlanjutan Usaha Peternakan Sapi Pedaging Skala Kecil di Daerah Lahan Kering: Studi Kasus di Kabupaten Bojonegoro - Arsalan Fadlan Aziz; Budi Hartono; Nanang Febrianto; Aulia Puspita Anugra Yekti; Eko Nugroho (Postgraduate, University of Mataram, 2026)
Climate change is an environmental issue and a major concern for the global community, impacting various sectors, including the livestock sector. This study aims to assess the sustainability of smallholder beef cattle farming businesses in dryland areas affected by climate change in Tambakrejo District, Bojonegoro Regency. The research method is a quantitative descriptive, involving direct field surveys and interviews with smallholder farmers. A total of 100 respondents were purposively selected with the criteria active members of a farmers’ group and having ≥ 1 cattle. The data analysis used was Rapfish with five dimensions, namely the ecological, economic, social, technological, and legal and institutional dimensions that are customized to the specific research area to provide an accurate representation of the present state. The results show that the ecological, economic, and technological dimensions are in quite sustainable category, and the social and legal and institutional dimensions are in highly sustainable category. Climate change affects forage and water availability, and drought frequency affects the sustainability score. Addressing these challenges requires enhanced ecological, financial support, and appropriate policy interventions. This study provides insights into resilience strategies for smallholder beef cattle farming aligned with SDG 2 (Zero Hunger) and SDG 13 (Climate Action) in Indonesia